Цілі, цінності й одиниця збереження біорізноманіття та генофондовий об’єкт у тваринництві - Гузєв, І.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. Definition of the purpose, values and units of preservation of a biodiversity, and also gene pool object in animal industries. Methods. On the basis of analysis SoW-AnGR, FAO, 2007b and modern base genetic knowledge we submit the general circuit of formation of an overall objective, the certain spectrum of values and preservation of their genetic basis – of the genofund (alleles pool) of agricultural animals. And as elementary unit of preservation acts, suggested by us, concept «gene pool object». Results. The purposes, values and units of preservation of a biodiversity are established, and also the concept is offered and definition «gene pool object» in animal industries is given. Conclusions. Combination of values selected for long-term preservation of set of populations, as well as specific value of each of them, can and should be based on the following categories (kinds or bases of values): economic, ecological (including landscape), historical, cultural, social, medical, scientific, and in the future – and on others, for the present the unknown to us. Basic unit of preservation of a biodiversity of animal industries is breed, and additional (auxiliary) – species (a sort or a subspecies), intrabreed (zonal) type (spawn), separate animals oustanding in the breeding attitude.

Key words: purposes, values and units of preservation, gene pool object.